The Influence of Cash Payments and QRIS (Quick Response Indonesia Standard) on Repurchase Intention at Boja Coffee & Roastery Bandar Lampung in the Digital Era - Intan, Melia Nur; RR. Erlina, RR. Erlina (Pascasarjana STIE Amkop Makassar, 2025)
This research examines how cash payments and QRIS (Quick Response Indonesian Standard) affect repurchase intention at BOJA Coffee & Roastery Bandar Lampung. Repurchase intention is a key sign of business longevity since repeat buyers give income stability. Customer-loyal companies are more robust to competition and market shifts. Digitalization in business has changed financial transactions, making non-cash payment alternatives more widespread. Quick Response Code Indonesian Standard (QRIS) is used by many industries to improve efficiency and customer service. This quantitative research employs questionnaires to obtain primary and secondary data from 232 Bandar Lampung BOJA Coffe & Roastery consumers. The association between cash payment, QRIS, and repurchase intention is examined using simple linear regression. The study found no significant impact of cash payments on repurchase intention, with a significance value of 0.068. On the other hand, QRIS payments have a positive and substantial impact (0.000).